Investigation of Leakage Current Waveforms Recorded in a Coastal High Voltage Substation - Pylarinos, D.; Siderakis, K.; Pyrgioti, E.; Thalassinakis, E.; Vitellas, I. (Engineering, Technology & Applied Science Research, 2011)
Leakage current monitoring is a widely employed technique to monitor the performance of outdoor insulation. The evaluation of leakage current waveforms recorded in the field, offers significant information since insulation’s performance is strongly linked with local conditions, and the waveforms’ shape correlate to different types of surface activity. In this paper, an investigation of leakage current waveforms recorded in a 150 kV coastal Substations suffering which suffers intense marine pollution is presented. Investigation of the recorded waveforms verified the basic waveform shapes described in the literature. Further, several variations of the basic types and complex waveforms, as well as field related waveforms, are presented. The need for added categorization criteria in the case of field measurements is discussed.